Natural formation of chlorobenzoic acids (CBA) and distinction between PCB-degraded CBA - Niedan, Volker Wolfgang; Schöler, Heinz Friedrich (Chemosphere, 1997)
Mono- and dichlorobenzoic acid (CBA) could be found in samples of remote bog pond water and sediment. The 2,4-CBA always had the highest concentrations. In bog water samples the concentrations ranged between 0.11 and 0.48 μg/I. Besides 2,4-CBA, most only 2,5-CBA could be found as dichlorobenzoic acid. In all samples we could detect also trichloroacetic acid (TCAA). The TCAA concentrations correlate with the CBA concentrations. As TCAA is known as a naturally produced organohalogen, this correlation can be seen as an indication to a natural formation of CBA. A confirmation of this presumption is our detection of CBA in a reaction of benzoic acid with the chlorinating enzyme chloroperoxidase (CPO).
Elektronische Reproduktion der Druck-Ausgabe vom 13. September 2000
Gesehen am 28.11.2022